Cash plus care: social protection cumulatively mitigates HIV-risk behaviour among adolescents in South Africa. - Cluver, L; Orkin, F; Boyes, M; Sherr, L (Lippincott, Williams and Wilkins, 2014)
OBJECTIVES: It is not known whether cumulative 'cash plus care' interventions can reduce adolescent HIV-infection risks in sub-Saharan Africa. This study investigated whether parental AIDS and other environmental adversities increase adolescent HIV-risk behaviour and whether social protection provision of 'cash' or integrated 'cash plus care' reduces HIV-risk behaviour. DESIGN: A prospective observational study with random sampling (<2.5% baseline refusal, 1-year follow-up, 96.8% retention). METHODS: Three thousand five hundred and fifteen 10-18 year-olds (56.7% girls) were interviewed in South Africa between 2009-2010 and 2011-2012. All homes with a resident adolescent were sampled, within randomly selected census areas in two urban and two rural districts in two provinces. Measures included potential environmental risks (e.g. parental HIV/AIDS, poverty), social protection: receipt of cash/food support (e.g. child grants, school feeding), care (e.g. positive parenting) and HIV-risk behaviours (e.g. unprotected sex). Analyses used logistic regression. RESULTS: Cash alone was associated with reduced HIV risk for girls [odds ratio (OR) 0.63; 95% confidence interval (95% CI) 0.44-0.91, P = 0.02] but not for boys. Integrated cash plus care was associated with halved HIV-risk behaviour incidence for both sexes (girls OR 0.55; 95% CI 0.35-0.85, P = 0.007; boys OR 0.50; 95% CI 0.31-0.82, P = 0.005), compared with no support and controlling for confounders. Follow-up HIV-risk behaviour was reduced from 41 to 15% for girls and from 42 to 17% for boys. Girls in AIDS-affected families and informal-dwelling boys had higher HIV-risk behaviour, but were less likely to access integrated social protection. CONCLUSION: Integrated cash plus care reduces male and female adolescent HIV-risk behaviours. Increasing adolescent access to social protection may be an effective HIV prevention strategy in Sub-Saharan Africa.